Remission of Psychosis in Treatment-Resistant Schizophrenia following Bone Marrow Transplantation: A Case Report - Miyaoka, Tsuyoshi; Wake, Rei; Hashioka, Sadayuki; Hayashida, Maiko; Oh-Nishi, Arata; Azis, Ilhamuddin Abdul; Izuhara, Muneto; Tsuchie, Keiko; Araki, Tomoko; Arauchi, Ryosuke; Abdullah, Rostia Arianna; Horiguchi, Jun (Frontiers in Psychiatry, 2017)
The authors present the case of a 24-year-old male with treatment-resistant schizophrenia, with predominant severe delusion and hallucination, who received bone marrow transplantation (BMT) for acute myeloid leukemia (AML). After BMT, he showed a remarkable reduction in psychotic symptoms without administration of neuroleptics. He also showed drastic improvement in social functioning. Follow-up evaluations two and four years after BMT showed persistent significant improvement of the psychotic state and social functioning. Recent findings show that the major underlying pathogenic mechanism of schizophrenia is immune dysregulation. Thus, conceptually, BMT, a cellular therapy, that facilitates the counteractive processes of balancing inflammation by immune regulation, could produce beneficial clinical effects in patients with treatment-resistant schizophrenia. Further studies are required to define the true benefits of BMT for the possible curative treatment of schizophrenia.